2021
DOI: 10.3390/medicina57080785
|View full text |Cite
|
Sign up to set email alerts
|

Iris-Claw Intraocular Lens: Anterior Chamber or Retropupillary Implantation? A Systematic Review and Meta-Analysis

Abstract: Background and Objectives: Iris-claw intraocular lens (ICIOL) could be implanted in the anterior chamber (AC) or retropupillary (RP) in eyes lacking capsular and/or zonular support. Several studies have focused on comparing the efficacy and complications of these two techniques and we designed this research to review the published literatures. Materials and Methods: Peer-reviewed studies were collected through network databases (PubMed, Scopus, Cochrane Central Register of Controlled Trials, and ClinicalTrials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 36 publications
0
6
0
1
Order By: Relevance
“…Nonetheless, the rate of CME seems to be lower than that of other techniques, often higher than 5% with iris claw. 31 Moreover, conjunctival or scleral erosions were observed in two studies. 11,22 This mostly occurred after IOL implantation without scleral flap creation.…”
Section: Discussionmentioning
confidence: 98%
“…Nonetheless, the rate of CME seems to be lower than that of other techniques, often higher than 5% with iris claw. 31 Moreover, conjunctival or scleral erosions were observed in two studies. 11,22 This mostly occurred after IOL implantation without scleral flap creation.…”
Section: Discussionmentioning
confidence: 98%
“…IOP elevation after IOL implantation has been reported in many studies 22 , 23 , and it is also commonly caused by postoperative steroid usage, anterior chamber inflammation, and pigment dispersion. Many studies revealed transient IOP elevation after surgery and these patients were treated with medication 12 , 14 , 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Verschiedene Studien berichteten, dass die präpupilläre Fixierung zur Aphakiekorrektur insbesondere bei flacher Vorderkammer zu einem Endothelzellverlust führen kann [15,16]. Ein Endothelzellverlust bei der retropupillären Fixierung ist aufgrund des Traumas im Rahmen des operativen Eingriffs beschrieben, durch die größere Entfernung vom Endothel im Vergleich zur präpupillären Fixierung ist ein chronischer Endothelschaden jedoch eher nicht zu erwarten [17,18].…”
Section: Irisfixierte Iol (Ifiol)unclassified
“…Several studies have reported that prepupillary fixation for aphakic correction can lead to endothelial cell loss, especially with a flat anterior chamber [15,16]. Endothelial cell loss during retropupillary fixation has been described due to trauma during the surgical procedure; however, chronic endothelial damage is not expected [17,18] due to the greater distance from the endothelium compared with prepupillary fixation.…”
Section: Iris-fixated Iol (Ifiol)mentioning
confidence: 99%